Estrategias didácticas participativas en la mejora del proceso enseñanza – aprendizaje de la Química. Año lectivo 2021-2022 - Jiménez Ludeña, Erick David (2022)
This Curriculum Integration research, explains the participatory didactic strategies from a constructivist approach, the fact of including this type of strategies in the classroom process makes evident the role of the student, as the main figure of the teaching-learning process of Chemistry. The aim of this work was to enhance the learning results in students, through the use of participatory didactic strategies, which allow to improve the teaching and learning process of Chemistry, in the first year of the BGU of "Bernardo Valdivieso" educational unit, academic year 2021 - 2022. The applied methodology was qualitative, because, throughout it, from the diagnosis, intervention and evaluation of results, relevant characteristics were determined around the implementation of constructivist teaching strategies. On the other hand, depending on the nature of the information, it corresponds to an action participatory research. Since, from the observed problem, it was proposed to enhance the learning results, through direct intervention, thus improving the teaching and learning process. For the development of the research, the problem was identified, firstly through research instruments and direct observation, after that, the intervention proposal was built and developed through micro curricular planning, which included the appropriate didactic material. Finally, to collect data, evaluation and research instruments were used. The most effective participatory teaching strategies, are cooperative learning, information analysis and problem solving, playful strategies, experimentation and project-based learning, among others. These participatory didactic strategies applied during the teaching-learning process of the Chemistry subject contributed to the consolidation of knowledge, for that the achievement of learning results in students was significantly enhanced. Keywords: Methodology, constructivism, chemistry experimentation, national curriculum